ANALISIS DAN PERANCANGAN SISTEM INFORMASI E-PROCUREMENT PADA P.D. CAKRAWALA BAN - Humdiana Roelly (Jurnal Informatika dan Bisnis, 2016)
Cakrawala Ban Trading Company’s E-Procurement was made out of PHP Hypertext Preprocessor version 5 by utilizing Code Igniter Framework. The author chose this particular programming language in consideration of ease of use, hence it can be used and modified by anyone else, and its open source nature, which means it’s free to obtain.This study resulted in the creation of e-procurement web application designed specifically for Cakrawala Ban Trading Company. This application can be accessed anytime anywhere through the use of computer or any internet connected, browser supported electronic devices. By using this application the owner can monitor the in and out of goods along with obtaining the best possible price offers which brought maximum profit to the company.From this study it can be concluded that through the use of e-procurement system, Cakrawala Ban Trading Company can provide convenience to the owner in terms of controlling the price of goods taken, acquiring accurate reports, and facilitate the staff in the process of searching the goods.Keywords : Procurement, Tire, Information System